Structure/function relationships in cellulolytic enzymes - Marc Claeyssens (浙江大学学报. 农业与生命科学版, 2004)
Cellulose and hemicellulose (mostly xylan), together with lignin, are the major polymeric constituents of plant cell walls and from the largest reservoir of fixed carbon in nature. The enzymatic hydrolysis of polymeric substances by extracellular enzymes, such as cellulases, hemicellulases and laccases, is preferred to chemical depolymerisation to avoid the production of toxic by-products and waste that are expensive to treat. The monosaccharides released through enzymatic hydrolysis can subsequently be microbially converted to commercial commodities, such as bio-ethanol (fuel extender) or microbial protein as feed supplements. The individual depolymerisering enzymes used, such as cellulases, xylanases and laccases, also have industrial application in (i) biobleaching in the paper and pulp industry, (ii) improvement of animal feed (poultry and ruminants) digestibility in feed industries, and (iii) dough rheology and bread volume in the baking process, and beer viscosity and filtration velocity during brewing. The cloning of the genes, coding for several xylan degrading enzymes, and their expression in Baker's yeast (Saccharomyces cerevisiae) and filamentous fungi (Aspergillus species) opened the possibility to study the pure enzymes, without contaminating activity.Trichoderma reesei produces several of these enzymes and detailed information on their specificity, synergies and structure/activity relationships is known. An overview will be presented.